The Impact of COVID-19 Policies on Nightlife in Kyoto - Koki Nozawa; Wenzhe Sun; Jan Dirk Schmoecker; Satoshi Nakao (Findings)
We use aggregate mobile phone statistics from people present in 500 m x 500 m meshes to analyse the change in nightlife population in central Kyoto. First, we quantify the impact of COVID policies, controlling for other seasonal factors, on each mesh with RegARIMA regression. Second, we explain these parameters with a spatial-lag regression that uses “points of interests” in these meshes as explanatory variables. We illustrate the spatial variation regarding the impact of the first COVID emergency declaration and of a so-called “Go-To campaign” that provided incentives for people to visit Kyoto. The results quantify the additional drop in visitors that meshes with more nightlife establishments experience due to COVID policies. The presence of take-aways, convenience stores etc instead reduces the impact at nighttime hours. The regression coefficients are small for the Go-To campaign model suggesting less recovery of nightlife activities.